Inheritance of Coat Colour in Ferrets (Mustela putorius furo) Based on Pedigree Analysis - Grabolus, Dominika; Wacławik, Patrycja; Zatoń-Dobrowolska, Magdalena (Polish Journal of Natural Sciences, 2021)
The study aimed to determine the rules governing the inheritance of coat colour in ferrets, including basic colour, colour concentration patterns, and white markings. To reach this aim, pedigree analysis was applied. It covered the pedigrees of 201 pups born between 2009 and 2017 in two household ferretries. In the analysed population, basic colours black and dark brown dominated over brown, beige, and those with copper reflections. The standard colour concentration pattern dominated the other patterns, the point type being the most recessive. The point pattern is phenotypically similar to the Himalayan mutation, which is also recessive to the wild type. In this study, it was impossible to analyse if the lack of white markings dominated over their presence, due to the small differences in the number of animals with and without white markings. The obtained results refer to a specific animal population and are based only on phenotypic classification.